Simulation and Implementation of Soft-Switched Interleaved DC-DC Boost Converter for Fuel Cell Systems - R. Seyezhai; Harinee Harinee; Nagarajan Nagarajan (Institute of Advanced Engineering and Science, 2012)
In this paper, a soft-switched Interleaved DC-DC Boost Converter (IBC) for fuel cell is simulated and implemented. The proposed two-phase IBC circuit consists of two identical boost converter connected in parallel and are controlled by interleaved switching signals. But in the conventional IBC switching loss increases with the number of switching devices. To solve this problem, this paper has proposed a soft switched IBC. Detailed analysis has been done to investigate the benefits of soft-switched IBC compared to that of conventional uncoupled and directly coupled IBC. The converter circuit is constructed using power MOSFET as power switch. The PWM is generated by PIC18F4450 microcontroller. In this paper, the analysis of the converter is presented which is verified by the results of simulation and experimentation.